2017
DOI: 10.1111/ijfs.13504
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, cooking quality, texture and consumer acceptance of pasta with Eruca vesicaria leaves

Abstract: In this study, pasta with dried Eruca vesicaria leaves commonly known as Rocket salad and spinach leaves flours were prepared. Samples were evaluated for its chemical composition, cooking quality, textural, colour and consumer acceptance. Results showed that pasta with Eruca vesicaria had the highest dietary fibre content (5.30–9.50 g/100 g) and the lowest fat content (2.13–2.80 g/100 g). The optimally cooked pasta with 5% of leaves (stored 30 days) and pasta with 10% of leaves (stored 14 days) have good cooki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
10
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 22 publications
7
10
2
Order By: Relevance
“…The values of carbohydrate content in enriched pasta were higher than those obtained by Barbara et al [2] for wheat spaghetti supplemented with silkworm flour (59.5 g/100 g). Protein values of tested pasta were slightly lower than those cited by Chillo et al [24] and Bouacida et al [16] for hard wheat spaghetti (13.5 g/ 100 g) and pasta enriched with Eruca leaves (18.74 g/100 g), respectively. According to Bouacida et al [16], the value found for fiber (5.50 < % fiber < 13.00%) allows pasta to be classified as a product with a high content of fiber.…”
Section: Chemical Composition Of Pastacontrasting
confidence: 60%
See 2 more Smart Citations
“…The values of carbohydrate content in enriched pasta were higher than those obtained by Barbara et al [2] for wheat spaghetti supplemented with silkworm flour (59.5 g/100 g). Protein values of tested pasta were slightly lower than those cited by Chillo et al [24] and Bouacida et al [16] for hard wheat spaghetti (13.5 g/ 100 g) and pasta enriched with Eruca leaves (18.74 g/100 g), respectively. According to Bouacida et al [16], the value found for fiber (5.50 < % fiber < 13.00%) allows pasta to be classified as a product with a high content of fiber.…”
Section: Chemical Composition Of Pastacontrasting
confidence: 60%
“…The pasta was manufactured according to the method presented by Bouacida et al [16]. Durum wheat pasta was made using commercial hard wheat semolina (La rose Blanche, Sousse, Tunisia), water, and different types of by-products (apple, pear, or date by-products).…”
Section: Pasta Manufacturingmentioning
confidence: 99%
See 1 more Smart Citation
“…The supplementation of pasta with other functional ingredients has received much attention. For instance, pasta has been fortified with protein-rich ingredients such as faba bean flour [ 17 ], meat [ 9 ], shrimp powder [ 18 ], green mussel powder (Perna canaliculus) [ 19 ], barely flour [ 20 ], amaranth seed flour [ 21 ], Eruca vesicaria leaves [ 22 ], artichoke canning by-products [ 23 ], almond flour [ 24 ], and Nannochloropsis sp. [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The researchers observed that starchprotein interactions increased with increasing levels of meat additions and accounted for decreasing glycemic responses. Also, interaction between starch-protein-phenolic compound in the food product affect protein structure through precipitation and decrease the starch and protein [22], artichoke canning byproducts [23], almond flour [24] and Nannochloropsis sp. [25].…”
Section: Introductionmentioning
confidence: 99%